2014
DOI: 10.1007/s12013-014-9925-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Physio-Biochemical Responses to Cold Stress in Tetraploid and Hexaploid Wheat

Abstract: The cellular changes induced by cold stress (CS) include responses that lead to oxidative stress and limits plant growth, metabolism, and productivity. In this study, responses of physio-biochemical to CS phases were comparatively studied in three genotypes of bread and durum wheats differing in sensitivity, two of them (Norstar, bread wheat and Gerdish, durum wheat) were tolerant to CS and the other one, SRN (durum wheat) was sensitive to CS. 14-day-old seedlings were subjected to CS (12 and 24 h) with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Consistent with previous studies (Xu et al, 2013), we found positive correlations between osmoprotectants (such as proline), protein and antioxidant enzyme activities (such as SOD, CAT, and peroxidase), suggesting a coordinated response between enzyme activity and protein synthesis. Moreover, we observed a negative association between antioxidants and damage indices (MDA and H 2 O 2 ), which is consistent with the concept that increased antioxidant capacity can lead to a reduction in ROS levels and oxidative stress (Xu et al, 2013; Nejadsadeghi et al, 2014; Ashraf et al, 2019; Hasanuzzaman et al, 2019). The physiological measurements between the cold tolerant and cold susceptible genotypes depicted the contrasting responses between the two groups.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (Xu et al, 2013), we found positive correlations between osmoprotectants (such as proline), protein and antioxidant enzyme activities (such as SOD, CAT, and peroxidase), suggesting a coordinated response between enzyme activity and protein synthesis. Moreover, we observed a negative association between antioxidants and damage indices (MDA and H 2 O 2 ), which is consistent with the concept that increased antioxidant capacity can lead to a reduction in ROS levels and oxidative stress (Xu et al, 2013; Nejadsadeghi et al, 2014; Ashraf et al, 2019; Hasanuzzaman et al, 2019). The physiological measurements between the cold tolerant and cold susceptible genotypes depicted the contrasting responses between the two groups.…”
Section: Discussionsupporting
confidence: 90%
“…The fatty acid analysis indicated that 18:3 linolenic acid is the major component (80% ) in leaves of durum wheat growing at 22°C, followed at a great distance by both saturated and unsaturated chains such as 16:0 and 18:2. This pro le agrees with that reported by (Nejadsadeghi et al 2014) using leaves of durum plants but differed from that obtained from durum grain samples in which 18:2 linoleic was the predominant fatty acid (Narducci et al 2019), suggesting tissue/organ speci c fatty acid patterns.…”
Section: Discussionsupporting
confidence: 87%
“…According to Yordanova and Popova (2007), exposure of wheat plants to low temperature (3 • C) for 48 and 72 h resulted in decreased levels of chlorophyll, CO 2 assimilation, transpirations rates and photosynthesis due to the reduced activities of ATP synthase, which further restricted RuBisCo regeneration and limited photophosphorylation (Allen and Ort, 2001). Physiobiochemical responses to cold stress in tetraploid and hexaploid wheat were studied where, the elevated levels of electrolyte leakage index, H 2 O 2 and MDA content were observed in stressed plants (Nejadsadeghi et al, 2014).…”
Section: Cerealsmentioning
confidence: 99%